1988
DOI: 10.1159/000163491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Gene Amplification Studied in Human Neuroblastoma Xenografts: Relationship with Tumor Growth Rate, Chemotherapeutic Sensitivities and Levels of Neuron-Specific Enolase

Abstract: Tumor doubling time, sensitivity to chemotherapeutic agents and concentrations of neuron-specific enolase were studied in nine human neuroblastoma xenografts, in which amplifications of N-myc, clones 8 and G21 were known; N-myc was amplified in eight, clone 8 in five and clone G21 in four of these nine xenografts. Tumor doubling time was longest in one xenograft, TNB10, which lacks the amplification of either N-myc or clone 8 or G21 and shortest in TNB1 in which all three DNA sequences are amplified with a DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Cytogenetic and molecular-biological investigations demonstrated that this xenograft showed an abnormal chromosome 1, a homogeneously staining resion (HSR) on chromosome 20, and 80-fold amplification of N-myc, 60-fold amplification of clone 8, and 100-fold amplification of clone G21 [21]. This xenograft was considered to be a representative of highly malignant human neuroblastomas with a short recorded tumor doubling time (4.8 days) [22]. A pilot chemosensitivity test showed that TNB9 is sensitive to cis-platinum but not to aclarubicin [22].…”
Section: Xeno-transplanted Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetic and molecular-biological investigations demonstrated that this xenograft showed an abnormal chromosome 1, a homogeneously staining resion (HSR) on chromosome 20, and 80-fold amplification of N-myc, 60-fold amplification of clone 8, and 100-fold amplification of clone G21 [21]. This xenograft was considered to be a representative of highly malignant human neuroblastomas with a short recorded tumor doubling time (4.8 days) [22]. A pilot chemosensitivity test showed that TNB9 is sensitive to cis-platinum but not to aclarubicin [22].…”
Section: Xeno-transplanted Neuroblastomamentioning
confidence: 99%
“…This xenograft was considered to be a representative of highly malignant human neuroblastomas with a short recorded tumor doubling time (4.8 days) [22]. A pilot chemosensitivity test showed that TNB9 is sensitive to cis-platinum but not to aclarubicin [22]. Effects of 15 other chemotherapentic agents on TNB9 are already known [ 18,191 according to the schedule of drug administration described below.…”
Section: Xeno-transplanted Neuroblastomamentioning
confidence: 99%
“…Establishment of neuroblastoma PDX models from primary tumour samples was first reported over 25 years ago [19][20][21] and has been described in more recent accounts. [22][23][24][25][26][27][28] Herein, we demonstrate the feasibility of developing high-risk neuroblastoma PDX models at a high success rate from multiple sources of tumour-bearing patient materials at both diagnosis and relapse and from primary and metastatic tumour sites, and for the first time, residual tumour cells from cytogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recent investigations have shown that the proliferative activity of the tumour represents an important prognostic parameter in neuroblastoma, being significantly correlated with the clinical outcome of the disease. [10][11][12][13] Moreover, a study carried out in a series of neuroblastoma xenografts demonstrated that the only tumour without N-myc amplification had the longest doubling time, 14 indicating that N-myc amplification might produce faster cell proliferation.…”
Section: N-mycmentioning
confidence: 99%